Kemauan Membayar Pelayanan Kesehatan Obstetri dan Faktor-faktor yang Mempengaruhi pada RS PKU Muhammadiyah Surakarta - Purbawati (Jurnal Kedokteran Indonesia, 2009)
Background: PKU Muhammadiyah Surakarta Hospital had an increasing account receiveable problemyear by year (2003 â 2006) that could interfere with hospital operation. Over 25% of total receivablesoccurred at obstetric units. Higher tariff to willingness to pay, but became known only after the use ofmedical services was concerned, would cause debt. This study aimed to estimate the willingness topay for obstetric health care and to determine factors that affect willingness to pay for obstetrichealth care.Methods: This was a descriptive and analytic study using cross-sectional design. Subjects were pregnantwomen who received antenatal care at PKU Muhammadiyah Surakarta Hospital. Samples were takenby purposive sampling technique. The data were collected using a questionnaire covering demographicand socio-economic characteristics, perceived service quality, and willingness to pay. Willingness topay was estimated by contingent valuation method, namely Bidding Game Technique. Effect of factorson willingness to pay was analyzed by linear regression model.Results: Multiple linear regression analysis showed that family income affects the willingness to pay onall classes in both normal deliveries and section caesaria. Perceived quality of service, education,number of parity, and the distance did not show statistically significant effect on willingness to pay forobstetric medical services.Conclusion: Household income increases willingness to pay for obstetric health care. Factors thatsignificantly affect the willingness to pay are family income. In this study, perceived quality of service,education, number of parity, and the distance showed no statistically significance effect.Keywords: willingness to pay, hospital